ASSESSMENT OF THE CLOPIDOGREL ACTION WITH REGARD TO CYP2C19 GENE POLYMORPHISMS IN PATIENTS WITH CORONARY ARTERY DISEASE AFTER IMPLANTATION OF DES STENTS - J. K. Uzokov; B. A. Alyavi; A. X. Abdullaev (Евразийский Кардиологический Журнал)
Aim of the work to assess the impact of CYP2C19 polymorphisms, including those of CYP2C19*1, CYP2C19*2, CYP2C19*3 and CYP2C19*17 on clopidogrel response variability in patients undergoing percutaneous coronary intervention (PCI) following DES implantation.